Hubungan Pola Makan dan Obesitas dengan Resiko Kejadian Rematik pada Lansia - Milzam Rafdi Asmara; Yusnika Damayanti; Dina Andriani (Universitas Malahayati, 2023)
ABSTRACT Rheumatism is one of the causes of joint pain that often occurs in the elderly. The impact of rheumatism is immobility for sufferers caused by several factors including diet and obesity. The aim of this study was to determine the relationship between diet and obesity with the risk of rheumatic events in the elderly at the Lawe Sigala Gala Kutacane Health Center. This research was conducted at the Lawe Sigala Gala Kutacane Health Center in August 2022 with a population of all elderly people in the working area of the Lawe Sigala Gala Kutacane Health Center and a sample of 61 people were taken using an accidental sampling technique. The research used a questionnaire and the data was processed using computerization. The results showed that more than half (73%) of the elderly had arthritis, more than half (74.4%) of the elderly had poor diet and less than half (44.3%) of the elderly were obese. The results of the chi square test showed a relationship between diet and obesity with the risk of rheumatic events in the elderly at the Lawe Sigala Gala Kutacane Health Center with a p-value ≤ 0.0. It is recommended that health centers optimize the provision of health education and prolanis activities for the elderly. Keywords: Diet, Obesity, Rheumatism, Elderly ABSTRAK Rematik merupakan salah satu penyebab nyeri sendi yang sering terjadi pada lansia. Dampak dari rematik yang ditimbulkan adalah imobilitas bagi penderita yang disebabkan oleh beberapa faktor diantaranya pola makan dan obesitas. Tujuan penelitian untuk mengetahui hubungan pola makan dan obesitas dengan resiko kejadian rematik pada lansia di Puskesmas Lawe Sigala Gala Kutacane. Penelitian ini dilaksanakan di Puskesmas Lawe Sigala Gala Kutacane pada Bulan Agustus 2022 dengan populasi seluruh lansia yang berada di wilayah kerja Puskesmas Lawe Sigala Gala Kutacane 154 orang dan sampel sebanyak 61 orang diambil dengan teknik accidental sampling. Penelitian menggunakan kuesioner dan data diolah dengan menggunakan komputerisasi. Hasil penelitian didapatkan lebih dari separoh (73%) lansia mengalami rematik, lebih dari separuh (74,4%) lansia pola makan buruk dan kurang dari separuh (44,3%) lansia dengan obesitas. Hasil uji chi square didapatkan hubungan antara pola makan dan obesitas dengan resiko kejadian rematik pada lansia di Puskesmas Lawe Sigala Gala Kutacane dengan nilai p-value ≤ 0,0. Disarankan kepada puskemas mengoptimalkan pemberian pendidikan kesehatan dan kegiatan prolanis pada lansia. Kata Kunci: Pola Makan, Obesitas, Rematik, Lansia